Impact of Capsulectomy Type on Post-Explantation Systemic Symptom Improvement: Findings From the ASERF Systemic Symptoms in Women-Biospecimen Analysis Study: Part 1. (16th December 2021) - Glicksman, Caroline; McGuire, Patricia; Kadin, Marshall; Lawrence, Marisa; Haws, Melinda; Newby, Jill; Ferenz, Sarah; Sung, James; Wixtrom, Roger
Abstract: Background: Breast Implant Illness (BII) is a term used to describe a variety of symptoms by patients with breast implants for which there are no abnormal physical or laboratory findings to explain their symptoms. There currently exists a difference of opinion among clinicians and patients concerning the diagnosis and treatment of patients self-reporting BII. Objectives: The first aim of this study was to determine if there is a valid indication for "en bloc" capsulectomy in patients self-reporting BII and if the type of capsulectomy performed alters long-term symptom improvement. The second goal was to identify any clinical laboratory differences between the cohorts. This study was funded by the Aesthetic Surgery Education and Research Foundation (ASERF). Methods: A prospective blinded study enrolled 150 consecutive subjects divided equally into 3 cohorts: (A) women with systemic symptoms they attribute to their implants who requested implant removal; (B) women with breast implants requesting removal or exchange who do not have symptoms they attribute to their implants; and (C) women undergoing cosmetic mastopexy who have never had any implanted medical device. The subject's baseline demographic data and a systemic symptoms survey, including PROMIS validated questionnaires, was obtained before surgery and at 3-6 weeks, 6 months, and 1 year. Blood was collected from all 3 cohorts and implant capsules were collected from Cohorts A and B. Results: 150 patients were enrolled between 2019-2021. Follow-up at 3-6 weeks for all 3 cohorts was between 98%-100%, 78%-98% at 6-months, and 1 year data is currently at 80%. The type of capsulectomy; intact total, total, or partial all showed similar symptom improvement with no statistical difference in the reduction of symptoms based on the type of capsulectomy. Conclusions: This study addresses one of the most discussed questions by plastic surgeons, patients, their advocates, and social media. The findings show that patients who self-report BII demonstrate a statistically significant improvement in their symptoms after explantation and that this improvement persists for at least 6 months. This improvement in self-reported systemic symptoms was seen regardless of the type of capsulectomy performed. Level of Evidence: 2: